Effectiveness of Peanut Shell Activated Charcoal as Adsorbent of Chromium and Lead Metal Ions Using Continuous System - Devi Heryanti; Susila Kristianingrum (Universitas Negeri Yogyakarta, 2025)
This study aims to determine the characteristics of peanut shell adsorbents based on SNI 03-3730-1995, the optimum conditions, efficiency and adsorption capacity of Cr and Pb metals in textile industry waste (simulated waste), and the morphology of the adsorbents. Peanut shells were converted into activated carbon by carbonization in a furnace at 450 °C for 5 minutes, then ground and sieved to a 60 mesh particle size. The carbon was chemically activated using a 0.5 M NaOH solution for 24 hours. Adsorption experiments employed a continuous system with variations in adsorbent mass (0.3, 0.6, and 0.9 grams), flow rate (slow and fast), and simulated Pb:Cr ratios (1:1, 1:2, and 1:3 (v/v)). The characterization results of activated carbon include moisture content of 3.99%, ash content of 7.46%, volatile matter content of 53.88%, iodine adsorption of 355.32 mg/g, and carbon content of 74.497%. Surface morphology showed porous structure with a pore diameter of 919.34 nm. The optimal conditions for the adsorption of Pb and Cr metals were an adsorbent mass of 0.9 g, slow flow rate, and a simulated waste ratio of 1:2. Adsorption efficiency for Cr and Pb metals was 73.33% and 100%, respectively, with adsorption capacities of 14.2902 mg/g and 2.0286 mg/g.